Three Dimensional Frameworks on News Entitled Papuan Student on Java Face Increased Pressures on The Jakarta Post - Friska Amalia (ELITE: Journal of English Language and Literature, 2019)
The news about Papuan students in Java that face increased pressure is a bad incident that once occurred in Indonesia. It is due to the students getting verbal attacks by mass organization and state apparatus. The research question of this study is “How did three dimensional frameworks reveal a case on news that entitled Papuan Students on Java Face Increased Pressures on The Jakarta Post ''. Therefore, this study is focused on revealing this case from the perspective of a critical discourse analysis by using Norman Fairclough’s approach (description, interpretation, and explanation). The method of this research is using a qualitative method in which the source data is the news text of The Jakarta Post. The results show description includes vocabulary and grammar. Those parts state that the majority group, namely FPI and Pemuda Pancasila and state apparatus perform unfair treatment by their vocabulary and grammar usage. Then, in the interpretation, it includes both production and consumption text. The Jakarta Post as the producer of the text news shows that it has pro-democracy value to point out that there are some indications of unfair treatment in Papuans student’s incident through the language written in the news text. Finally, the explanation includes situational, institutional, and social level. This stage shows that social, political, and cultural aspects of a society influences the production of the The Jakarta Post news text.